The train has left the stadion: real estate price effects of mainline realignment in Berlin - Gabriel M. Ahlfeldt (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
While there is an increasing body of literature testing for a correlation between access to regional markets and economic activity, little evidence is available for market access being of causal importance for economic development. This paper investigates the impact of exogenous variation to cities and regions on an urban scale. We study the case of Berlin where the western central business district unexpectedly became disconnected from long-distance railway connections. A combined hedonic and difference-in-difference approach is employed to show that property transaction prices within areas identified to experience a particularly strong decline in accessibility are reduced by approximately 22% after announcement of a new transport plan. We show that this treatment effect is not attributable to effects other than variation of access to cities and regions.
Keywords: R11; R12; R21; R40; R53; R58; 330; Market access variation; hedonic model; difference-in-difference; railway system; Berlin